2012
DOI: 10.1074/jbc.m112.348813
|View full text |Cite
|
Sign up to set email alerts
|

Menaquinone-7 Is Specific Cofactor in Tetraheme Quinol Dehydrogenase CymA

Abstract: Background: CymA is the central menaquinol-7 dehydrogenase in anaerobic respiration of Shewanella sp.Results: CymA uses menaquinone-7 as a cofactor.Conclusion: CymA has one cofactor site that is specific for menaquinone-7 and one low affinity Q/QH2 site that is in equilibrium with the quinone pool.Significance: The function of quinones needs to be reevaluated and crystallographically determined quinone binding pockets might not be the site of quinone conversion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
94
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(100 citation statements)
references
References 66 publications
4
94
1
1
Order By: Relevance
“…For instance, in this journal Gao et al (2009) assumed that electron transfer between CymA and NapAB is direct and does not involve a further electron shuttling protein. Other researchers raised the hypothesis that CymA would form electron transfer complexes with the outer membrane anchored terminal reductases MtrABC or DmsABEF (Ross et al, 2011;McMillan et al, 2012). Nevertheless, this study reveals the necessity of at least one connecting protein, either FccA or STC for coupling respiratory oxidation of CymA to effective electron transfer to at least ferric citrate, DMSO and nitrate.…”
Section: Discussionmentioning
confidence: 63%
“…For instance, in this journal Gao et al (2009) assumed that electron transfer between CymA and NapAB is direct and does not involve a further electron shuttling protein. Other researchers raised the hypothesis that CymA would form electron transfer complexes with the outer membrane anchored terminal reductases MtrABC or DmsABEF (Ross et al, 2011;McMillan et al, 2012). Nevertheless, this study reveals the necessity of at least one connecting protein, either FccA or STC for coupling respiratory oxidation of CymA to effective electron transfer to at least ferric citrate, DMSO and nitrate.…”
Section: Discussionmentioning
confidence: 63%
“…In this study, the detected outer membrane cytochrome c genes included decaheme OmcA/MtrC (Richter et al, 2012a), MtrF (a homologue of OmcA/MtrC) (Coursolle and Gralnick, 2010), and OmpA. Periplasmic multi-heme cytochrome c including one decaheme MtrA, 11 decaheme DmsE (a homologue of MtrA) (Coursolle and Gralnick, 2010), 3 inner membrane anchored (periplasm side) tetraheme NapC/NirT (a homologue of quinol dehydrogenase CymA) (McMillan et al, 2012) and 2 transmembrane high-molecular-weight cytochrome electron-transferring complexes were detected (Fig. 7).…”
Section: C-type Cytochrome Genes Suggest Direct Electron Transfermentioning
confidence: 97%
“…At neutral pH, the RP window of MtrC/OmcA, MtrF, MtrA and CymA are À0.5 to 0.1 V, À0.4 to 0.1 V, À0.3 to 0 V and À0.4 to 0 V, respectively (Clarke et al, 2011;Firer-Sherwood et al, 2008;McMillan et al, 2012;Ross et al, 2011). Supply of the periplasmic electrons acceptor fumarate to a Shewanella oneidensis MR-1 formed biocathode (poised at À0.36 V) immediately led to electrons uptake for fumarate reduction, while a mutant lacking MtrA, MtrB or the menaquinone-linked CymA displayed a severe reduction deficiency, which showed that electrons primarily flowed from outer membrane cytochromes into the menaquinone pool, and then back to periplasmic fumarate reductase (Ross et al, 2011).…”
Section: C-type Cytochrome Genes Suggest Direct Electron Transfermentioning
confidence: 99%
“…Protein film electrochemistry of multi-haem cytochromes from S. oneidensis. Cyclic voltammetry of CymA (solid line) adsorbed on an 8-mercaptoctanol modified template stripped gold electrode at a 10 mV s 21 scan rate, pH 7.4 is compared to a voltammogram recorded in the absence of CymA (broken line) (redrawn from [34]). Baseline-subtracted cyclic voltammograms are presented for MtrCAB, MtrA, MtrC and MtrF adsorbed on graphite electrodes.…”
Section: Redox Potentialsmentioning
confidence: 99%